Comment on S Memon, et al. (J Pak Med Assoc. 74: 1163-1166, June 2024) Osmolar gap in hyponatraemia: An exploratory study - Muhammad Ramish Irfan, (Journal of the Pakistan Medical Association, 2025)
Madam, Your paper about the osmolar gap in hyponatraemiawas much appreciated as it remains a subject shrouded inmisunderstanding.The observations reported in this paper are certainly thoughtprovoking, therefore I would extend a few conceptualclarifications that I believe your readership would benefit fromin gaining deeper insight about the findings reported in thisstudy.The difference between tonicity, osmolarity and osmolality isoften disregarded and appears convoluted however, it is crucialto delineate between these terms nevertheless. Tonicity inparticular requires special consideration as it denotes behaviourof solutions, relative to each other, separated by a semipermeablemembrane. As such, it would be more appropriate touse the term osmolality or osmolarity to describehyponatraemia in your study. Osmolality and osmolarity aredenoted by a specific unit of measurement (mOsm/kg andmOsm/L respectively) and are thus better suited to describedysnatraemias.1 Additionally, considering the high proportion of hyperosmolarhyponatraemic patients in your study, the paper would havebenefitted from an outlining of the percentage of these thatwere due to hyperglycaemia, especially since patients withcomorbid type 2 diabetes mellitus were a considerable majorityin your sample. This, alongside statistical correlation betweensuch variables, would have strengthened your argument byhighlighting a potential non-alcohol related cause for higher OGin hyponatraemic patients.Moreover, the lack of elaboration on specific characteristics ofpatients with higher OG and in particular those that sufferedmortality to further elucidate significance of OG in variousclinical contexts was also noticeable. However, this only opensopportunity for further robust research by your team. Continued..